Pengaruh Kinerja Keuangan terhadap Harga Saham Sebelum dan Selama Pandemi Covid-19 pada Perusahaan Sub Sektor Farmasi di Bursa Efek Indonesia - Wahyu Hidayat; Kiagus Andi; Neny Desriani (E-journal Field of Economics, Business and Entrepreneurship (EFEBE), 2022)
The Impact of Financial Performance on Share Prices Before and  During the Covid-19 Pandemic in Companies in the Pharmaceutical Sector of the Indonesian Stock Market The independent variables of this study, Return On Assets (ROA) and Earnings Per Share (EPS), were tested for their positive effect on stock prices. We use research samples of 144 pharmaceutical companies with observational data on the Indonesian Stock Exchange in 4 years. The test tool for this study is multiple linear regression analysis processed by E-views 12. The research results showed that Return On Assets (ROA) had a negative effect on the stock prices and Earnings per Share (EPS) had a positive effect on the share prices of IDX companies in the pharmaceutical sector.